Recent Progress in the Chemistry of Mucohalic Acids: Versatile Building Blocks in Organic Synthesis - Zhang, Ji; Sarma, Koushik Das; Curran, Timothy T. (Synlett, 2013)
This account documents our recent progress in exposing some of the potential of mucohalic acids in synthetic applications. Understanding their stability and reactivity in different reaction media allows the development of mild and regioselective methods to access various substituted butenolides, butenolactams, and 4,5-dihalopyridazin-3(2H)-ones and to create other novel, multifunctionalized building blocks.1 Introduction2 The Rationale for the Reinvestigation of Mucohalic Acid Chemistry3 Understanding the Stability of Mucohalic Acids4 One-Pot Synthesis of a 4,5-Dihalopyridazin-3(2H)-one and the Process Chemistry of ABT-9635 Reductive Amination of Mucochloric Acid and Synthesis of Antiseizure Drug Levetiracetam (Keppra)6 Reduction of Mucohalic Acids and Synthesis of Anti-inflammatory Agent Rofecoxib (Vioxx)7 Lewis Acid Catalyzed Knoevenagel Aldol Reaction8 Lewis and Brønsted Acid Promoted Friedel–Crafts Hydroxyalkylation9 Lewis Acid Facilitated Mukaiyama Aldol Reaction10 Indium-Mediated Allylation in Water11 Palladium-Free Regioselective Etherification and Amination12 Novel Building Blocks Derived from Mucohalic Acids 13 Direct Vinylogous Aldol Addition Using α,β-Dihalo-Substituted Butenolides and Butenolactams14 Other Applications15 Summary and Conclusion
Keywords: mucohalic acids; butenolides; γ-lactones; γ-lactams; building blocks